Effect of Adding Different Active Substances on Inhibition Zone Diameter and Microstructural Properties of Composite Bioplastics - Permatasari, Nelsy Dian; Witoyo, Jatmiko Eko; Susilo, Donor Utomo M.; Saraswati, Ayu Rahayu; Masruri; Yuwono, Sudarminto Setyo; Widjanarko, Simon Bambang (Jurnal Pangan dan Agroindustri, 2025)
This study identifies the phytochemical compounds in ethanolic extracts of Syzygium myrtifolium leaves, applies it to developing composite bioplastics as a natural antibacterial agent, and compares it with composite bioplastics prepared with sodium benzoate, particularly regarding inhibition zone diameter and microstructure. The results showed that the phytochemicals were identified in the ethanolic extract of Syzygium myrtifolium leaves, like flavonoids, alkaloids, tannins, phenolics, terpenoids, and saponins. LC-MS confirming bioactive in it as auraptenol, calopiptin, quercetin-3-O-β-D-glucuronide, and quercetin-3-O-L-arabinopyranoside. Moreover, in vitro tests showed that composite bioplastics with the ethanolic extracts of Syzygium myrtifolium had inhibition zone diameter against E. coli, similar to those with sodium benzoate added. Additionally, the microstructure of the composite bioplastics with the ethanolic extracts of Syzygium myrtifolium was rougher, irregular, and more porous than those of another. It indicated that the ethanolic extract of Syzygium myrtifolium leaf could be used as a natural antibacterial agent to replace the chemical agent.